Munculnya Krapyak dan Perubahan Lingkungan di Mataram pada Abad ke-17 - Afwakhoir, Rifki (Universitas Gadjah Mada, 2024)
Humans have been hunting animals for thousands of years. Hunting activities can no longer be seen as simply killing animals. Hunting has such a broad meaning. In the 17th century, Mataram kings did hunting as a habit in krapyak. This name of area is a large area surrounded by a wooden fence filled with animals. The Mataram kings could freely hunt without fearing being attacked by wild animals. The king’s habit of hunting in krapyak was often thought of merely as a pastime. This research attempts to scrutinize the effect of the development of krapyak environmental change at Mataram in the 17th century through literature study. Then, the study used both resources, primary and secondary historical data. An anthropocentric approach and materialism-historical analysis were used to understand the damage caused by the development of krapyak and the environmental change that occurred. This research shows that hunting in krapyak is not merely seen as a king’s pastime, but also affirms territorialization and implicitly legislates wildlife ownership. The presence of it also indicated environmental changes in the Mataram area in the 17th century.